Piezoelectric Sensor for Human Pulse Detection - Kalange, A.E.; Gangal, S.A. (Defence Science Journal, 2007)
Diagnosis according to Ayurveda is to find the root cause of a disease. Out of eight differentkinds of examinations, nadi-pariksha is very important. By checking the pulse, the Ayurvedicphysician finds the predominant dosha out of the three - vata, pitta and kapha. Nadi-parikshais done at the root of the thumb by examining the radial artery. Presently, this technique issubjective and the accuracy of the diagnosis depends upon the expertise of the Ayurvedicphysician. As a first step towards making the diagnosis by nadi-pariksha objective, humanpulse detection and processing system has been developed.Piezoelectric sensor was used for human pulse detection. The pulse signals obtained fromthe piezoelectric sensor were processed through signal processing circuitry. The signal provessingcircuit consists of signal amplifier, filters, and noise-reduction circuit. The signal processingcircuit has been designed, built, and tested. The performance of the developed system wasevaluated by recording the pulses of people (subject) having different doshas. Pulse shapes,repetition rate, amplitude were found to be different for people having different doshas.Performance of the signal processing circuit and the pulse waveforms obtained have beenpresented and analysed.